HUBUNGAN TINGKAT DISABILITAS PASIEN STROKE DENGAN RESPON BERDUKA KELUARGA DI RUANG RAWAT INAP RSD GUNUNG JATI KOTA CIREBON - Nonok Karlina; Siti Nuraina Inayah; Putri Gayuh Uthami (Jurnal Kesehatan Mahardika, 2018)
Background: Stroke is the disease cause of disability in the world. The disability impact on the individual functions in performing daily activities and impact on the family too. Nuclear families whose family members suffered brain disorders such as stroke, showed> 50% experience depression, suicide, weakness and anxiety. The psychological effect is called by the grieving response. Purpose: The purpose of this study was to determine the relationship of the level of disability of stroke patients with family grieving response. Method: This research type is analytic descriptive with cross sectional approach The sample of this research was family from stroke patient in hospital ward of Gunung Jati Hospital Cirebon with 30 respondents using purposive sampling technique. The instruments were used observation sheets and questionnaires. Data analysis using chi square test. Result: The results showed no significant relationship between the level of disability with family grief response was shown with the results p value was 0.260 or > α (0.05) which means Ha rejected. In addition to providing care to the patient, the nurse is expected to participate in involving the family by providing positive support as a protective response of mourning.